Usability Evaluation of the UT Radio Website of Universitas Terbuka Using the System Usability Scale (SUS) Method - Jamaludin Jamaludin; Candra Wibawa; Bachriah Fatwa Dhini; Garza Fahrizal (Universitas Wiralodra, 2026)
The UT Radio website is one of Universitas Terbuka’s digital innovations that serves as a medium for disseminating academic information, distance learning, and educational entertainment for the academic community. However, its usability level has not yet been empirically evaluated. This study aims to analyze user satisfaction and usability quality of the UT Radio website using the System Usability Scale (SUS) method. A descriptive quantitative approach was employed, involving 60 respondents consisting of students, lecturers, and administrative staff of Universitas Terbuka. Data were collected through observation, interviews, and the SUS questionnaire, which includes ten statements measured on a five-point Likert scale. The analysis was conducted based on SUS scores interpreted with adjective ratings, grade scale, and acceptability range. The findings show that the average usability score of the UT Radio website is 74, which falls into the “Good” category, with a C grade and an “Acceptable” level of acceptance. This indicates that the system has met aspects of ease of use, efficiency, and user satisfaction. Nevertheless, improvements are still required in several aspects, such as interface consistency, access speed, and feature interactivity. This research provides practical contributions for e-learning system developers and higher education digital media managers in improving user experience quality for web-based services.